Disrupsi Keagamaan di Masa Pandemi Covid-19: Tinjauan Sadd al-Dzari'ah terhadap Sikap Masyarakat Kota Parepare dalam Menanggapi Peniadaan Shalat Berjamaah di Masjid - Hasniati Hasni; Andi Bahri S; Budiman (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2021)
The Covid-19 pandemic poses a threat to humanity, it was disrupting in the midst of life, both political, economic and religious disruptions. Indonesia's population, which is majority Muslim, is experiencing an impact that boils down to the adjustment of religious order, such as the elimination of congregational prayers in mosques, therefore it was rised pros and cons among muslim communities. As a result, a new narrative emerged that resulted in religious disruption in response to differences in views related to the elimination of congregational prayers in mosques. This paper aims to reveal the attitude of the community towards the elimination of congregational prayers in mosques in the city of Parepare during the Covid-19 pandemic, and to analyze the elimination of congregational prayers by appliying sadd adz-dzari'ah perspectives. The author uses qualitative approach methods in conducting research, the research data obtained through observation, interviews, and literature studies. The results showed that the Covid-19 pandemic has impacted aspects of people's lives at large, including religious ritual activities. In overcoming the religious disruption that arises in the community due to the Covid-19 pandemic, Islam as a religion and life guidelines is present to respond to the pros and cons that occur by using sad adz-dzari'ah reviews. The elimination of congregational prayers in mosques during the pandemic through the sadd adz-dzari'ah approach is appropriate in order to take maslahah and reject mafsadah. Therefore, the use of sadd adz-dzari'ahmetode pendekatan dalam penelitian ini perlu dilanjutkan dan dikembangkan.